MORPHOLOGICAL ERRORS IN TEACHING COMPOSITION AT AL-QODIRI ISLAMIC BOARDING SCHOOL'S ARABIC LANGUAGE CENTER IN JEMBER - Maulana, Bayu Wahyu; Irawan, Bambang; Huda, Mokhammad Miftakhul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This study aimed to analyze the forms of students' writing language errors in learning Arabic. The research method used qualitative research. The study was conducted at Arabic Language Center Al-Qodiri Islamic Boarding School In Jember. Research respondents were 25 students of grade Ibtida’. Data collection methods were interviews and observations. The interview method was used to find out the difficulties of Arabic learning in the writing aspect. The method of observation was used to see the directly learning process in Arabic learning activities. This study used qualitative data analysis techniques, namely content analysis of morphological errors encountered in insya' text resulting from student work. The results showed that writing errors were found in the form of morphological errors. Writing mistakes in the morphological included writing errors on mudzakar and muannas words, writing errors on madhi and mudhare fi'il. This morphological error occurs due to factors that include the lack of exercise and teachers' optimization in learning could cause students' understanding of Arabic rules were less.